HUBUNGAN KEPATUHAN DENGAN KEJADIAN ADVERSE DRUG REACTIONS (ADRS) PADA PENGGUNAAN ANTIBIOTIK BETA-LAKTAM DI RSUD BENDAN KOTA PEKALONGAN - Fatina, Naila; Musa Fitri Fatkhiya (Universitas Pekalongan, 2024)
Background: Beta-lactam antibiotics are one of the most common drugs to treat bacterial infections. Although effective, the use of these antibiotics can cause Adverse Drug Reactions (ADRs), potentially affecting patient compliance with treatment. Non-adherence in the use of antibiotics can have a negative impact on therapeutic outcomes, including an increased risk of ADRs. Objective: The research aims to determine the relationship between compliance and the incidence of ADRs in the use of beta-lactam antibiotics at Bendan Hospital, Pekalongan City. Method: This research used prospective method (Cohort). The sampling technique used was non probability sampling with purposive sampling method, where samples were taken from outpatients who used beta-lactam antibiotics at Bendan Hospital, Pekalongan City period November. Data were collected through structured interviews and MMAS-8 questionnaires to assess the level of patient compliance and Naranjo Algorithm questionnaires to assess the incidence of ADRs. After data collection, the data were analyzed using SPSS software with chi-square test to determine the relationship between compliance and the incidence of ADRs. Result: The results showed that there were 30 patients using beta-lactam antibiotics with 9 patients who experienced ADRs. The results of the Naranjo Algorithm questionnaire obtained were respondents with a degree of certainty of highly probable 6 respondents (20%), probable 3 respondents (10%), possible 9 respondents (63.3%), and doubtful 2 respondents (6.7%). The most common form of manifestation of ADRs was skin rash as many as 3 respondents (33.3%). While the results of the compliance questionnaire obtained 22 respondents in the high category (73.3%), 8 respondents in the medium category (26.7%), and 0% in the low category. The results of the analysis of the relationship between compliance with the incidence of ADRs on the use of beta-lactam antibiotics obtained a ρ-value of 0.305> 0.05 which indicates there is no relationship between compliance with the incidence of ADRs on the use of beta-lactam antibiotics. Conclusion: There is no association between compliance and the incidence of ADRs in the use of beta-lactam antibiotics Keywords: ADRs; Beta-lactam antibiotics; Adherence.